"The process of depicting a still life consisting of geometric shapes" (Eurasian Journal of Humanities and Social Sciences, 2022)
This article provides information on depicting a still life made of geometric shapes made of plaster. along with the exercises done in the auditorium, it is important to make a sample of these geometric shapes at home from vatman paper and describe them by creating different compositions with the participation of two, three, four objects. By placing and lighting the shapes in different situations, the artist's spatial and volume knowledge and imagination develop